2019
DOI: 10.1093/rheumatology/key332
|View full text |Cite
|
Sign up to set email alerts
|

B cells in Sjögren’s syndrome: from pathophysiology to therapeutic target

Abstract: Biological abnormalities associated with B lymphocytes are a hallmark of patients with primary Sjögren’s syndrome. Those patients present abnormal distribution of B lymphocytes in peripheral blood and B cells in exocrine glands. B cells produce auto-antibodies, cytokines and present antigens but can also suppressive functions. In this review, we will summarize current knowledge on B cells in primary Sjögren’s syndrome patients, demonstrate their critical role in the immunopathology of the disease and describe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 146 publications
0
34
0
Order By: Relevance
“…We have been investigating the possible involvement of BAFF in the pathogenesis of pSS because BAFF plays a pivotal role in B cell activation [7,11,13,15] and is involved in the pathogenesis of diseases associated with antibody formation, such as pSS. For example, several groups have reported that BAFF levels are elevated in the serum of pSS patients [16][17][18] and that this elevation is correlated with the patients' serum IgG and autoantibody levels, such as anti-Ro/SSA and anti-La/SSB antibodies [19,20]. Moreover, BAFF is strongly expressed in lymphocytes that infiltrate the salivary glands [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…We have been investigating the possible involvement of BAFF in the pathogenesis of pSS because BAFF plays a pivotal role in B cell activation [7,11,13,15] and is involved in the pathogenesis of diseases associated with antibody formation, such as pSS. For example, several groups have reported that BAFF levels are elevated in the serum of pSS patients [16][17][18] and that this elevation is correlated with the patients' serum IgG and autoantibody levels, such as anti-Ro/SSA and anti-La/SSB antibodies [19,20]. Moreover, BAFF is strongly expressed in lymphocytes that infiltrate the salivary glands [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, rituximab therapy failed to show a benefit in two clinical trials despite the compelling evidence supporting the key roles of B-cells in disease pathogenesis, such as the high prevalence of autoantibodies and hypergammaglobulinemia, the presence of germinal center–like structures in salivary gland biopsies, the increased risk of non-Hodgkin’s B-cell lymphoma, and genetic studies linking the risk for pSS with polymorphisms in genes critical for B-cell development 7, 8 . The optimism for targeting B-cells was fueled by promising results in early pilot studies of rituximab in pSS 911 .…”
Section: Clinical Trials In Primary Sjögren’s Syndrome: Coming Up Drymentioning
confidence: 99%
“…Despite the failure of rituximab therapy to show a benefit in the TEARS and TRACTISS trials, B-cells remain a focus of interest in the treatment of pSS. A host of studies has demonstrated alterations in peripheral and tissue-resident B-cell subsets, genetic and epigenetic modifications in B-cells, and B-cell microRNA expression profiles 8 . BAFF may promote B-cell over-activation and loss of tolerance in pSS.…”
Section: Identifying Mechanistically Based Therapeutic Targetsmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, these autoantibodies have been shown to play a pathogenic role (4,7). Besides the occurrence of these autoantibodies, SjS patients are characterized by deep alterations in the frequency of several B lymphocyte populations, both in the blood and in the infiltrated exocrine glands (8)(9)(10). Another hallmark of the disease is the B cell hyperreactivity due to chronic antigenic stimulation, which is initially polyclonal but can progress to monoclonal B cell lymphoproliferation.…”
Section: Introductionmentioning
confidence: 99%